How does one extract many-body interatomic potentials from ab-initio band structure calculations - Gurskii, Z.; Krawczyk, J. (Condensed Matter Physics, 1999)
An original approach to the ab-initio deriving many-body interatomic potentials in metals is discussed. It is based on calculating the Kohn-Sham total
energy functional using the pseudopotential method. The local density approximation (LDA) is shown to be applied, within the pseudopotential concept, to the analysis of the valence electron kinetic energy. Utilizing the LDA
and linear superposition assumption for total electron density enables us to
treat the exchange-correlation and kinetic energies of valence electrons in
terms of contributions to indirect many-body interactions. Equations for the
pair and for the triplet potentials in metals are given. Relationship between
the method developed and other approaches is analyzed. Викладено підхід, в основі якого лежить використання методу псевдопотенціалів та формалізму Кона-Шема. Показано, як у наближенні
локальної густини можна записати обмінно-кореляційну та кінетичну
енергії валентних електронів у вигляді внесків у непрямі (опосередковані) багаточастинкові взаємодії. Аналізується зв’язок розвиненого підходу з відомим способом отримання міжатомних потенціалів у
рамках теорії збурень за псевдопотенціалом. Подано явні вирази для
парних і тричастинкових потенціалів.